New faiths, old fears : Muslims and other Asian immigrants in American religious life - Lawrence, Bruce B. (Columbia University Press, 2002)
As a result of immigration from Asia in the wake of the passage of the 1965 Hart-Celler Immigration Act, the fastest-growing religions in America -- faster than all Christian groups combined -- are Islam, Hinduism, Buddhism, and Sikhism. Now a leading scholar asks how these new faiths have changed or have been changed by the pluralist face of American civil society and by the deep-rooted American ambivalence toward foreign traditions.
Keywords: United States -- Religion -- 1945-; Asians -- United States -- Religion.; Immigrants -- Religious life -- United States -- History -- 20th century.; États-Unis -- Religion -- 1945-; Asiatiques -- États-Unis -- Religion.; 11.84 Islam: other.; RELIGION -- Religious Intolerance, Persecution & Conflict.; RELIGION -- Islam -- History.; Asians -- Religion; Immigrants -- Religious life; Religion; United States; Asiaten; Muslim; Religiöses Leben; USA; Multikulturelle Gesellschaft; Muslims.; Immigrants.; Religion.; United States.; Kulturell assimilation -- religiösa aspekter -- Förenta staterna.; Förenta staterna -- asiatiska influenser.; Asiaten.; Since 1900; History